Impact of Exogenous Proteolytic Enzymes on Immunogenesis in Patients with Urogenital Infections - A. A. Khryanin; O. V. Reshetnikov; I. D. Safronov (Антибиотики и Химиотерапия, 2020)
The use of systemic enzyme therapy in combination with antibiotics in the treatment of urogenital chlamydia infection in patients of both sexes proved to improve the therapeutic efficacy and to reduce the risk of the side effects.